MILLENNIAL GENERATION AND GENERATION Z'S RECEPTION OF THE EXISTENCE OF PANCASILA IN THE 45 CONSTITUTION ON THE INDONESIAN INSTITUTE OF PANCASILA IDEOLOGY YOUTUBE CONTENT: A Case Study at BPIP - Turusi, Iskandar; Ronda , Andi Mirza; Widowati , Dewi (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2021)
This study delivers into the reception of Pancasila ideology through the YouTube platform by the Indonesian Institute of Pancasila Ideology (BPIP RI). The focus of this research is to understand why BPIP has chosen YouTube as the primary channel for spreading Pancasila ideology and to identify the challenges faced in this process. Additionally, this study aims to elucidate the audience's position in responding to the content conveyed by BPIP via YouTube. Drawing on Stuart Hall's reception analysis concept and Lasswell's model, this research seeks to explore how audiences respond to and understand Pancasila ideology messages and their impact on society. A qualitative approach is employed to provide the appropriate methodological foundation for exploring related social phenomena. A case study is chosen as it allows for a more detailed analysis of how Pancasila ideological messages are, received, and processed by YouTube audiences, as well as the factors influencing this process. Providing giveaways or scholarships for schooling and higher education from BPIP RI. It is hoped that by implementing these recommendations, efforts to disseminate Pancasila ideology can more successfully strengthen awareness and commitment to Pancasila values in Indonesian society.